Crop preference of farmers in Passi City - Fernandez, Yran B. (2003)
A study to assess the crop preference of farmers in Passi City was conducted in the five selected barangays where the 85 farmer respondents are engaged in the production of various agricultural crops like rice, corn, pineapple, vegetables, coffee, mango, bananas and coconut. The purpose of the study ws to find out the preferred crops of the farmers and the reasons for their preference. The survey and descriptive method of research with the interview schedule as the gathering data instruments was used in the study. The 85 respondents were made to choose their most preferred crop in terms of estimated yield levels, technology used, production period, production cost and production return. The findings show that the most preferred crop of the farmers is rice with vegetables and bananas as second and third preferences, respectively. For the farmers, rice has the highest average yield from among the crops listed because the production gives them higher returns compared with other crops. a majority of the farmers use integrated farming, high yielding variety of rice and organic farming. Twenty-five percent of the farmers are still using traditional farming methods inspite of the advent of modernization in areas that could not be reached by irrigation. It can therefore be concluded, that rice is the preferred crop by the farmers of Passi City considering all the factors involved in the study. In this connection, it is recommended that farmers be encouraged to plant high yielding varieties of rice o increase their production and derive higher income thus compensating their efforts and production cost. The Department of Agriculture should intensify information dissemination drive on the proper planting technology of other viable crops in Passi City that could be planted after rice is harvested. Pineapple, corn, coffee, bananas and vegetables should be encouraged as alternative crops considering their economic values to the farmers.
[Research Paper] (Mgt 299). -- [Iloilo City] : UPV-CM, August 2003.